ANALISIS WACANA FEMINIS TOKOH SRINTIL DALAM TRILOGI RONGGENG DUKUH PARUK KARYA AHMAD TOHARI - Yulia, Elisa Linda; Kebayantini, Ni Luh Nyoman; Nugroho, Wahyu Budi (JURNAL ILMIAH SOSIOLOGI (SOROT), 2017)
ABSTRACT Â The aims of this study are to determine the feminism contains of the Ronggeng Dukuh Paruk Trilogy novel by Ahmad Tohari, to understand the position of Srintil character as subject, object, the author's viewpoint as well as the reader's viewpoint which based on the feminist discourse analysis method by Sara Mills. The results of discourse analysis on Ronggeng Dukuh Paruk novel show that Srintil placed as subject because of her superiority in economic, social, and psychological as well as successfully opposing the social order which restricting her expression of life, which rejecting all rules of â€œperonggenganâ€ sphere. At her position as an object, shown Srintil while she was flirted, touched on her body, maligned, scorned, threatened by her status as a ex-prisoner, more over she used as a tool or a doll to meet the demand of actors around her, either in material or satisfying the desires of men. In the author's viewpoint, Ahmad Tohari is also more inclined to show Srintil as an object position by a lot of sentence structure which using herself and Rasus figure as the first person pronoun, so as the main character, Srintil can not tell her own self. Meanwhile, according to the readerâ€™s viewpoint, Srintil figure shown more in the object position than the subject position. Therefore, the general Srintil be in a position subordinate object because of itâ€™s position as a result of the image that has made Srintil interpreted belongs to anyone, so he experienced violence and physical and psychological oppression. Keyword; Feminist discourse analysis, Ronggeng Dukuh Paruk, Srintil